2014
DOI: 10.4103/0019-5049.147146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of femoral nerve block and intravenous fentanyl for positioning during spinal anaesthesia in surgery of femur fracture

Abstract: Background:Spinal anaesthesia is the preferred technique to fix fracture of the femur. Extreme pain does not allow ideal positioning for this procedure. Intravenous fentanyl and femoral nerve block are commonly used techniques to reduce the pain during position for spinal anaesthesia however; results are conflicting regarding superiority of femoral nerve block over intravenous fentanyl.Aims:We conducted this study to compare the analgesic effect provided by femoral nerve block (FNB) and intra- venous (IV) fent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 12 publications
1
53
0
Order By: Relevance
“…This was found to be in accordance in other similar studies. Jadon et al, who used lignocaine as the nerve blocker also found similar results as Sia et al and Gosavi et al 8,21,20 But Iamaroon et al did not find any significant difference in the two types of analgesia. It has been estimated that this could be due to the fact that he used bupivacaine instead of lignocaine as FNB.…”
Section: Discussionsupporting
confidence: 71%
“…This was found to be in accordance in other similar studies. Jadon et al, who used lignocaine as the nerve blocker also found similar results as Sia et al and Gosavi et al 8,21,20 But Iamaroon et al did not find any significant difference in the two types of analgesia. It has been estimated that this could be due to the fact that he used bupivacaine instead of lignocaine as FNB.…”
Section: Discussionsupporting
confidence: 71%
“…1,14 Also, many authors while comparing FNB with other modalities for positioning for central neuraxial block found FNB to be superior to all other modalities. 3,4,6,12,14 The drug used for the block also has a significant difference on the duration and results as shown in study conducted by Iamaroon et al, did not find much advantage of FNB over other modalities as bupivacaine was used instead of lignocaine. The effect of lignocaine in FNB comes in 5 minutes.…”
mentioning
confidence: 65%
“…3 Also, any overriding of the fracture ends causes deformity and is extremely painful. Delay in positioning further aggravates pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and S2 show the characteristics of the included studies. Eight studies [10][11][12][14][15][16][17][18] were RCTs, and two studies [13,19] observational studies. These studies were performed in Positioning of femur fracture patients for spinal block PLOS ONE | https://doi.…”
mentioning
confidence: 99%